E-MODULE DEVELOPMENT USING 3D PAGEFLIP PROFESSIONAL WITH IBSE (INQUIRY BASED SCIENCE EDUCATION) APPROACH IN STATIC FLUID MATERIALS - Latifah, Sri; Diani, Rahma; Anisa, Nava (BIOCHEPHY: Journal of Science Education, 2024)
The study aims to develop a physics e-module on static fluids using 3D PageFlip Professional with an Inquiry-Based Science Education (IBSE) approach. The research employed a Research and Development (R&D) method following the ISI-ARE model, which includes investigate, strategy, improve, assessment, realization, and estimation stages. The e-module was validated by experts in materials, media, and language, achieving high feasibility ratings. Material validation averaged 93%, media validation 94%, and language validation 95%, all categorized as "very feasible." Educator responses to the e-module indicated an average score of 94% under "very interesting" criteria. Small group trials showed an 86% score, and field tests yielded 91%, both under "very interesting" criteria. These results demonstrate the e-module’s effectiveness and potential to enhance physics learning using an innovative digital format.